SYNTHESIS OF EOSIN Y-SENSITIZED Ag-TiO2 NANO-HYBRID FOR OPTIMIZED PHOTOCATALYTIC DEGRADATION OF AQUEOUS CAFFEINE - Muktar Musa Ibrahim; Umar Ibrahim Gaya (Journal of the Chilean Chemical Society, 2019)
The visible light spectral response of titania nanoparticles synthesized by hybrid treatment of TiO2 with silver dopant and Eosin Y-sensitizer was evaluated using caffeine, an emerging pollutant. The photocatalyst was characterized using scanning electron microscopy (SEM), x-ray diffraction (XRD), solid state UV/ Visible spectrometry and Fourier transform infrared spectrometry (FTIR). Upon sensitization and doping, downsizing, increase in surface area and redshift were observed without significant annihilation of the tetragonal anatase and rutile structures. Factors affecting the degradation of caffeine were studied using Taguchi orthogonal array model and optimized using a response surface methodology (RSM) based on faced-centered composite design (FCCD). Caffeine degradation under the conditions of the study was not affected significantly by temperature but pH, initial concentration and catalyst concentration. Evidence for electron injection and red shift with sensitization was corroborated using quantum calculations at DFT/B3LYP level of the theory.